Sobre la pobreza cultural de una práctica (judicial) sin teoría - Ibáñez, Perfecto Andrés (2017)
The traditional model of initial training of judges in Spain and in other countries has been focused, and is still focused, on the mechanical digestion of a pile of stereotyped notions related to several legal subjects.This knowledge is presented with no references to specific legal disputes and does not meet at all, neither the profile of modern complex constitutional legal systems consisting of several levels, internally changing and conflicting; nor the practice of those systems. It does correspond, however, the historical model of the Napoleonic judge, who tends to act as a mechanical enforcer of the law and the longa manu of the real power rather than guardian of the citizens’ basic rights. The alternative to this kind of judicial training would be a system of training incorporating a high quality operative knowledge of the positive law actually in force, together with a theoretical-philosophical training in line with the suggestions made by Manuel Sacristán of «a level of exercise of thinking» based on the specific field and activity inherent to that group of legal practitioners.